Etika Pemerintahan dalam Perspektif Core Values ASN Berakhlak di Indonesia - Nurmiyati, Niken; Alaydrus, Anwar; Loilatu, Mohammad Jafar; Rafdi, Hashfi (International Journal of Demos (IJD), 2025)
This study examines government ethics from the perspective of the core values of ASN BerAKHLAK in Indonesia. The Indonesian government has established ASN BerAKHLAK core values as a standard for civil servants to strengthen ethics in public service. This research aims to analyze the implementation of the values of Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative in government practices. A qualitative descriptive approach was used in this study. The findings reveal that as of July 2024, the total number of civil servants (ASN) in Indonesia, consisting of PNS and PPPK, has reached 4,758,730 individuals. This reflects the dynamic development of bureaucracy in terms of the number of civil servants, regional distribution, educational background, and dominant generational composition, analyzed through the lens of ASN BerAKHLAK core values. Efforts such as strict regulations, training programs, and strengthening a work culture based on integrity while optimally implementing BerAKHLAK values are expected to achieve good governance.